Environmental governance through guidance: The 'making up' of expert practitioners. (June 2015) - Cashmore, Matthew; Richardson, Tim; Rozema, Jaap; Lyhne, Ivar
Highlights: Critically examines environmental governance as a site for contesting power and authority. Employs a governmentality perspective to analyze the 'making up' of expert practitioners. Problematizes the taken for granted strategy of governing through guidance. Finds widely varying constructions of the skills, values and conducts expected of expert practitioners. Concludes with reflections on the implications for environmental governance and power research. Abstract: Political power has received curiously limited attention within the vast literature on environmental governance. This article addresses this research lacuna by employing a particular perspective on power – governmentality – to examine the environment as a site for the contestation of power and authority. Our empirical focus is the 'making up' (after Hacking (1986)) of expert practitioners through an apparently innocuous governance strategy: the publication of non-binding guidance documents. Qualitative document analysis is undertaken to elucidate how the identities of expert practitioners are constituted in guidance documents published under the auspices of powerful actors (the World Bank, the Danish Ministry of Environment and the Dutch Commission for Environmental Assessment) operating at various geospatial scales and within particular political contexts. The publication of guidance is interpreted as a purposeful attempt to problematize and reframe practices. The skills, values and conducts that expert practitioners are expected to reproduce and the desires and aspirations of those that would govern are analyzed and discussed. These vary widely in the case study guidance, from the constitution of the practitioner as agential policy entrepreneur radically intervening in political systems in developing countries in the guidance published under the auspices of the World Bank to the expert practitioner as a mediator of supranational political influence, and hence national authority, in the Danish case. The analysis raises a number of conceptual and empirical questions about the strategy of governing through guidance, and the article concludes with recommendations for further research to better comprehend the taken for granted miniature of the machinery of environmental governance.